Konsep Pendidikan Perspektif Al-Qur'an: Kajian Tematik - Muh. Muhyiddin; Ibnu Chudzaifah (Al-Fikr: Jurnal Pendidikan Islam, 2021)
The Qur'an lays down the teachings of monotheism or divinity in the one and only God, where every human being must be responsible to him, eradicating social and economic crimes from the lowest level to the highest level. The concept of Islam in the educational process and overcoming ignorance is found in the Qur'an and Sunnah. Islam is present as a religion that provides instructions in which the context of the holy book directs it so that its people do not become ignorant people. For Muslims, believing in the Qur'an as a way of life is a form of obligation and religion whose rights are Islam. But in reality, now the concepts in the Qur'an are not fully realized in education in the community. As in society, education and teaching have been carried out, but there are still many children and even adults who do not have morals or etiquette with fellow humans both to teachers and parents, or even their souls are not trained to be able to accept what the teacher teaches to make them a good person. noble. There are many realities in the life of a society in terms of education that are still left behind, those who still put aside learning and choose to work to fulfill their lives and even just fulfill their lifestyle. There are many possibilities that they are not aware and understand the importance of learning to seek knowledge or even left behind the discourse about knowledge. This study aims to look at the concept of education from the perspective of the Qur'an. The type of research used is descriptive qualitative literature (library research). The data collection technique used by the researcher is to collect data from various library sources, both from books, journals, seminar results, and discussions with experts relevant to the research theme. The conclusion of this study is that the Qur'an reveals the term education with many terms including al-Tarbiyah, al-Ta'lim, al-Tazkiyah, al-Tadris, al-Tafaquh, al-Ta'aqul, al-Tadabbur, al-Tadzkirah, al-Tafakkur, al-Mau'idza. The purpose of education in Islam wants the formation of a Muslim who has integrity in his personality, the goodness of his speech is also manifested in good behavior, all of which are a reflection of the cleanliness of his heart.